The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11207-014-0616-5
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Global Survey of Coronal Null Points from Potential-Field-Source-Surface (PFSS) Modeling and Solar Dynamics Observatory (SDO) Observations

Abstract: This article compiles and examines a comprehensive coronal magneticnull-point survey created by potential-field-source-surface (PFSS) modeling and Solar Dynamics Observatory/Atmospheric Imaging Assembly (SDO/AIA) observations. The locations of 582 potential magnetic null points in the corona were predicted from the PFSS model between Carrington Rotations (CR) 2098 (June 2010) and 2139 (July 2013). These locations were manually inspected, using contrast-enhanced SDO/AIA images in 171Å at the east and west solar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 47 publications
2
24
1
Order By: Relevance
“…In general, similar coronal loop formations have been attributed to there being a null point at the 'X' (e.g. [4,5]); however, it is possible that a separator may be present instead.…”
Section: Basic Elements Of the Three-dimensional Magnetic Skeletonmentioning
confidence: 88%
See 2 more Smart Citations
“…In general, similar coronal loop formations have been attributed to there being a null point at the 'X' (e.g. [4,5]); however, it is possible that a separator may be present instead.…”
Section: Basic Elements Of the Three-dimensional Magnetic Skeletonmentioning
confidence: 88%
“…In about 31% of the cases, Freed et al [5] found that the AIA observations showed structures, such as X-type loop patterns, that could be interpreted as the configuration associated with a null point. However, since separators are field lines that generally extend from or to a null point, it is not unreasonable to imagine that in a proportion of the above cases, the coronal signature may reveal the location of a separator, rather than a null point.…”
Section: Basic Elements Of the Three-dimensional Magnetic Skeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this method, Eriksson et al (2015) performed a statistical study of magnetic nulls in the nightside magnetosphereand concluded that the number of spiral nulls prevailed over the number of radial ones. The global potential field extrapolations allowed us to locate a large number of magnetic nulls in the solar corona (Edwards & Parnell 2015;Freed et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Cook, Mackay, and Nandy (2009), they found that the most nulls occurred during solar minimum when extensive regions of mixed small-scale field are present on the solar surface. Freed, Longcope, and McKenzie (2015) also directly identified null points in PFSS extrapolations of the global corona. However, their PFSS extrapolations have a low resolution, with an l max = 30.…”
Section: Introductionmentioning
confidence: 88%